Emotional Stability of Nurses and its Relation to Their Job Crafting - Ehsan S. S. Saad; Faten M. Ahmed (Evidence-Based Nursing Research)
Context: Emotional stability is the process in which the personality is continuously striving for a greater sense of emotional health. Job crafting and can be seen as a specific form of proactive behavior in which the nurse initiates changes (redesign) in the level of job demands and job resources to make their job more meaningful. Nurses with high emotional stability are more tending to adapt to changes in their job and enhance their job crafting.